Simultaneously Removal of Tar and Dust by Emulsion Liquid Membrane. Issue 3 (May 2019) - Dong, Pengxiong; Zhang, Junjie; Sun, Yekun; Li, Hongxia
Abstract: The new method for removal of tar and dust from coke oven flue gas by emulsion liquid membrane was investigated. The emulsion liquid membrane consists of kerosene as membrane solvent, L-113B as surfactant, distilled water as internal phase and external phase. Effect of different operating parameters such as L-113B concentration, volume ratio of oil phase to internal phase, volume ratio of emulsification speed were investigated on the removal efficiency of tar and dust from coke oven flue gas. Optimum operating conditions were obtained and the tar removal efficiency can reach up to 98.32% and the dust removal efficiency can reach up to 96.37%.